The Influence of Abiotic Environment and Connectivity on the Distribution of Diversity in an Andean Fish Fluvial Network - Herrera-Pérez, J.; Parra, J. L.; Restrepo-Santamaría, D.; Jiménez-Segura, L. F. (Frontiers in Environmental Science, 2019)
Abstract The distribution of Andean freshwater fishes is the result of the interaction of historical and contemporary factors such as basin geomorphology and the physicochemical characteristics of the water bodies. Dramatic changes along the river network due to waterfalls or dams generate dramatic changes in longitudinal slopes and fish assemblages because they function as ecological barriers to dispersal. We expect the amount of variation in beta diversity along the elevation gradient (between 700 and 3,500 m a.s.l.) of the eastern slope of the Cauca River basin to be explained by changes in the water environment and connectivity among sites. We measured connectivity in terms of the distance in the stream channel between sampling sites considering changes in slope. We used a Generalized Dissimilarity Model (GDM) to evaluate the contribution of connectivity and other water mass characteristics (dissolved oxygen, pH, conductivity, temperature, and elevation) in predicting changes in beta diversity. The GDM models explained 33% of the total variance in species turnover, suggesting that there are additional variables that have not been considered, such as available habitats along the rivers. Elevation was the variable with the largest relative importance in the model and connectivity only explained seven percent of the total variance when all sites were included. However, when only the sampling sites in the stream headers were included (most geographically isolated sites), the contribution due to connectivity increased to 51%. Isolation of stream headers, in conjunction with extreme conditions such as low water temperature, may influence the fish assemblage turnover. Our results provide evidence that elevation has a strong influence on beta diversity of Andean fish assemblages. Species turnover upstream above 1,200 m a.s.l. is strongly influenced by channel connectivity and there are additional environmental variables that need to be included in the models to improve their prediction power.